ANALISIS KORESPONDENSI UNTUK MENGETAHUI VARIABEL UNGGULAN (STUDI KASUS PADA MALL PANAKKUKANG, MALL TRADE CENTER, DAN MALL RATU INDAH). - Ermawati, Ermawati; Fajaruddin, Muhammad (Jurusan Matematika FST-UIN Alauddi Makassar, 2014)
Correspondence analysis is a technique of data presentation between rows, between columns and between rows and columns of contingency tables (twoway which can then be extended to multi-way contingency table) at a smalldimensional vector space and optimal. This analysis is also designed to be used in the development of groupings that represent the data frequency.The purpose of this analysis is to determine the relevant attributes that meet the perceived similarity between objects MP, MTC and MaRI, as well as the flagship of the categories of variables determining the attributes and object categories. The data used in this study is the primary data using a questionnaire research instrument. The results of correspondence analysis found that the MP has the advantage of the diversity of the counter (25%), and the architecture of the building gives the percentage of 20% compared to the other. Later in the MTC has the advantage in a row on the location and condition of access to toilet facilities with a large percentage of 22% and 21%. MaRI has the advantage of very high compared to the MP and MTC in terms of access to the location with the percentage of 33%. Results The study concluded that if you want to find a quality product and a counter that varies with the architecture satisfying the MP is the right choice to visit, where the level of satisfaction about the quality of its products by 65%, the diversity of the counter by 75% and 78% of building architecture, but if you want to feel the atmosphere of peace and security both inside the mall, the MTC is a fitting choice for the enjoy, where the percentage of MTCs satisfaction in terms of composure by 27% and 28% security.